Improvement of students critical thinking skills through structured inquiry learning models on substance pressure topics - Lina Ihtimamin Nashoihah; Tutut Nurita (Jurnal Pijar Mipa, 2022)
The study aimed to describe improving students' critical thinking skills by applying a structured inquiry model to the substance pressure topic. The research design is one group pretest-posttest design. The study was conducted at the eighth-grade junior high schools in Surabaya in the 2021/2022 academic year, which totaled 22 respondents. Data collection techniques in questionnaire and test. The questionnaire analysis used the Guttman scale, which was calculated using the percentage formula. While the data analysis techniques pretest-posttest using N-Gain score, normality test, and paired t-test. An implementation of the structured inquiry model improves students' critical thinking skills. It is shown that the t-test where the significance value of (0.000 <0.05) indicates differences in students' critical thinking skills before and after the structured inquiry model is applied. The average value of Gain evidence the difference-the results were (0.81) in the high category, and 91% of the 22 students experienced increased critical thinking skills in the high category. The implementation of learning using the inquiry model gets a mode value of 4, so it can be categorized as very good. The students gave a response reaching 93.96% in the very good category. In conclusion, a structured inquiry model can improve students' critical thinking skills on substance-pressure topics.